APPROCHE SÉMI0- STYLISTIQUE DE LA PRIÈRE : : « JE VOUS SALUE MARIE » - Hakizimana, Jean – Bosco Mujarugamba; MUNYAKABERA, ASS Innocent BAGARAGAZA (IJRDO - Journal of Social Science and Humanities Research, 2023)
In this modest work, our preoccupation is to establish the semantic reports between the prayer in one and the reflection of his/her/its indications. By his/her/its discursive strategy of doubled flattery of the semiotics and the stylistics, the Gabriel archangel wishes to be ambassador, door - speech of the human beings, of the people in general. He/it exhorts his/its interlocutor to pray for the people so that the one - recovers life here.